Praktik Akuntansi Manajemen dan Kinerja Usaha Mikro Kerajinan di Kabupaten Bondowoso pada Masa Pandemi - Putri, Devani Nindia; Wafaretta, Vega (Jurnal Ilmiah Wahana Akuntansi, 2022)
Micro handicraft businesses in Bondowoso Regency have also felt the impact of the Covid-19 pandemic, so they have to manage production costs. Therefore, the purpose of this study is to determine the impact of management accounting practices (budgeting, cost system, and performance evaluation) on the performance of micro handicrafts businesses in Bondowoso Regency in 2021. In this study, a questionnaire instrument to measure management accounting practices and performance was modified in accordance with the scale of micro-enterprises. Data collection was carried out by distributing questionnaires directly to forty (40) respondents who owned micro-craft businesses. Data processing used multiple linear regression analysis. The results of data processing show that budgeting and performance evaluation encourage the performance of micro-enterprises. Meanwhile, the cost system cannot boost the performance due to the inability of micro businesses to reduce and manage operational costs, resulting in a decrease in profits. Micro businesses are adapting to the conditions of the Covid 19 pandemic, including focusing on online sales, compiling budgets, monitoring production costs, as well as evaluating employee and financial performance.